A conserved host and pathogen recognition site on immunoglobulins: Structural and functional aspects - Wines, B.; Trist, H.; Farrugia, W.; Ngo, C.; Trowsdale, J.; Areschoug, T.; Lindahl, G.; Fraser, J.; Ramsland, Paul (2012)
A common site in the constant region (Fc) of immunoglobulins is recognized by host receptors and is a frequent target of proteins expressed by pathogens. This site is located at the junction of two constant domains in the antibody heavy chains and produces a large shallow cavity formed by loops of the CH2 and CH3 domains in IgG and IgA (CH3 and CH4 domains in IgM). Crystal structures have been determined for complexes of IgG-Fc and IgA-Fc with a structurally diverse set of host, pathogen and in vitro selected ligands. While pathogen proteins may directly block interactions with the immunoglobulins thereby evading host immunity, it is likely that the same pathogen molecules also interact with other host factors to carry out their primary biological function. Herein we review the structural and functional aspects of host and pathogen molecular recognition of the common site on the Fc of immunoglobulins. We also propose that some pathogen proteins may promote virulence by affecting the bridging between innate and adaptive immunity.